(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objectives: We investigated the impact of birth weight on early childhood caries (ECC) to identify the association between birth-related factors and oral health using Korea’ national health screening database. Methods: Children born between 2008 and 2012 who had undergone the first and second health screening at least once and had been confirmed ECC through ECC examination in the first to third oral health screening were included. They were classified according to the presence of dental caries (ECC or non-ECC group) and their birth weight (low [LBW; <2,500 g] or normal birth weight [NBW; 2,500–4,000 g]). We analyzed the association of multiple variables with ECC and examined the impact of birth weight on ECC by logistic regression and log binomial modeling to determine the odds ratio (OR) and relative risk (RR). Findings: ECC prevalence among the 47,633 included infants and children was approximately 29%. Logistic regression and log binomial modeling showed that the OR and RR for ECC were 0.82 (95% CI, 0.73-0.91) and 0.86 (95% CI, 0.79-0.94), respectively, for children with LBW against those with NBW. Conclusions: Our results indicated that LBW is not a risk factor for ECC. ECC is a preventable disease for which early detection is crucial. Therefore, oral health screening programs for infants and children should be further promoted to prevent oral diseases and improve oral health.